Wuzang Wenyang Huayu decoction regulates differentially expressed transcripts in the rats' hippocampus after cerebral hypoperfusion - Xia, Meng (J Cell Mol Med, 2019)
The modified Wenyang Huayu decoction has been widely used to treat vascular dementia in China for thousands of years. We have previously proved that a modified version, Wuzang Wenyang Huayu decoction has the potential to be a more effective clinical treatment that can attenuate cerebral ischaemic injury. However, the global transcript profile and signalling conduction pathways regulated by this recipe remains unclear. This study established a two‐vessel occlusion rat model by bilateral common carotid artery occlusion. Two groups of rats were intragastrically treated Wuzang Wenyang Huayu 2.5 g/kg vs or Piracetam 0.15 g/kg for 2 weeks. Learning and memory abilities were measured with Morris water maze. Neuronal plasticity was observed by HE staining. Differentially expressed transcripts of rat hippocampus were analysed by transcriptomics with Illumina HiSeq2500 platform. Results showed that Wuzang Wenyang Huayu decoction significantly alleviated learning, memory deficits, coordination dysfunction and prevented hippocampus cellular injury; Results further revealed the increased gene expression in KEGG metabolic pathways (MT‐ND2. MT‐ND3, MT‐ND4, MT‐ND4L, MT‐ND5 and MT‐ATP8) and genes involved in signal transduction, carcinogenesis, immune system, endocrine system, nervous system etc (Results further revealed differential expression of genes involved in various systems, including MT‐ND2) Our discovery is likely to provide new insights to molecular mechanisms of Wuzang Wenyang Huayu regarding hippocampal transcripts in a murine vascular dementia model.